Testing sand and soil from selected playgrounds in Lublin for eggs of nematodes of the genus: Ascaris, Toxocara, Trichuris - Chodun-Wroblewska Wiktoria; Nieradko-Iwanicka Barbara; Iwanicki Janusz Andrzej (Current Issues in Pharmacy and Medical Sciences, 2022)
Children need to play outdoors. It is a natural tendency for young children to put everything in their mouths. Hygienic condition of playgrounds is important for maintaining their health. Companion animals (dogs and cats) as well as wild animals can transmit parasites that cause zoonoses in humans. Such infections often affects children playing in sandpits and playgrounds. Sand samples taken from specific locations (sandboxes, playgrounds) can be tested for the presence of parasite eggs specific to humans and animals (Ascaris, Toxocara, Trichuris). They cause ascariasis, toxocarosis, trichurosis. Invasive eggs of the parasites due to the very thick, multi-layered egg shells are very resistant to the influence of climatic factors and to chemicals present in the environment. The only way to get rid of parasite eggs from locations where they endanger human health is to remove the top layer of sand or soil or completely replace the sand. However, this is a laborious and costly procedure.